Quantitative assessment of UML dynamic models. - Baroni, Aline Lúcia (Software engineering notes.)
In this work we plan to provide a suite of measures to address mainly two problem areas within contemporary object-oriented software measurement: (i) the lack of measures for the early stages of system development, like conceptual modeling and (ii) the lack of measures for dynamic models of an object-oriented system. Our suite of measures is going to be taken from UML 2.0 diagrams. OCL (Object-Constraint Language) and the UML 2.0 meta-model will be used to formalize and contextualize the definitions.